Attitudes toward deprescribing among adults with heart failure with preserved ejection fraction. Issue 7 (12th May 2021) - Navid, Pedram; Nguyen, Linh; Jaber, Diana; Zarzuela, Kate; Musse, Mahad; Lu Wang, Marcos; Requijo, Tatiana; Kozlov, Elissa; Masterson Creber, Ruth M.; Hilmer, Sarah N.; Lachs, Mark; Goyal, Parag
Abstract: Background/Objectives: Attitudes toward deprescribing could vary among subpopulations. We sought to understand patient attitudes toward deprescribing among patients with heart failure with preserved ejection fraction (HFpEF). Design: Retrospective cohort study. Setting: Academic medical center in New York City. Participants: Consecutive patients with HFpEF seen in July 2018–December 2019 at a program dedicated to providing care to older adults with HFpEF. Measurements: We assessed the prevalence of vulnerabilities outlined in the domain management approach for caring for patients with heart failure and examined data on patient attitudes toward having their medicines deprescribed via the revised Patient Attitudes Toward Deprescribing (rPATD). Results: Among 134 patients with HFpEF, median age was 75 (interquartile range 69–82), 60.4% were women, and 35.8% were nonwhite. Almost all patients had polypharmacy (94.0%) and 56.0% had hyperpolypharmacy; multimorbidity (80.6%) and frailty (78.7%) were also common. Overall, 90.3% reported that they would be willing to have one or more of their medicines deprescribed if told it was possible by their doctors; and 26.9% reported that they would like to try stopping one of their medicines to see how they feel without it. Notably, 91.8% of patients reported that they would like to be involved in decisions about their medicines. In bivariate logistic regression, nonwhite participants were less likely to want to try stopping one of their medicines to see how they feel without it (odds ratio 0.25, 95% confidence interval [0.09–0.62], p = 0.005). Conclusions: Patients with HFpEF contend with many vulnerabilities that could prompt consideration for deprescribing. Most patients with HFpEF were amenable to deprescribing. Race may be an important factor that impacts patient attitudes toward deprescribing.